On a subclass of the class of generalized Douglas-Weyl metrics - A. Tayebi; E. Peyghan (Հայաստանի ԳԱԱ)
We study the class of Finsler metrics whose Douglas curvature is constant along any Finslerian geodesics. This class of Finsler metrics is a subclass of the class of generalized Douglas-Weyl metrics and contains the class of Douglas metrics as a special case. We find a condition under which this class of Finsler metrics reduces to the class of Landsberg metrics. Then we show this class of Landsberg metrics contains the class of R-quadratic metrics.
Keywords: Mathematics; Science